1990
DOI: 10.1111/j.1365-3091.1990.tb00627.x
|View full text |Cite
|
Sign up to set email alerts
|

The variability of critical shear stress, friction angle, and grain protrusion in water‐worked sediments

Abstract: The erodibility of a grain on a rough bed is controlled by, among other factors, its relative projection above the mean bed, its exposure relative to upstream grains, and its friction angle. Here we report direct measurements of friction angles, grain projection and exposure, and small‐scale topographic structure on a variety of water‐worked mixed‐grain sediment surfaces. Using a simple analytical model of the force balance on individual grains, we calculate the distribution of critical shear stress for ideali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
499
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(523 citation statements)
references
References 24 publications
22
499
2
Order By: Relevance
“…Figure 10 shows an example the fractional rating curves for the J21 sediment. The results in this and related figures [25] [6] indicate that the model is generally able to infer a reference stress distribution that produces predictions consistent with the observations. While the rating curves generally seem to be appropriate, there is one suspect rating curve, that for the 32.0 mm size fraction.…”
Section: Bulk Transportsupporting
confidence: 64%
See 1 more Smart Citation
“…Figure 10 shows an example the fractional rating curves for the J21 sediment. The results in this and related figures [25] [6] indicate that the model is generally able to infer a reference stress distribution that produces predictions consistent with the observations. While the rating curves generally seem to be appropriate, there is one suspect rating curve, that for the 32.0 mm size fraction.…”
Section: Bulk Transportsupporting
confidence: 64%
“…Kirchner et al [25] observed that for a given sediment mixture, a multiplicity of bed configuration and transport rates are possible. This phenomenon, while understood and widely accepted, has no general solution.…”
Section: Motivation and Implementation On New Datasetsmentioning
confidence: 99%
“…Good progress has been made in describing these over the last decade (Kirchner et al 1990;Buffington et al, 1992Johnston et al, 1998and McEwan and Heald, 2001. Nevertheless, to date, these descriptions are entirely empirical (or numerical) and their acquisition requires considerable effort in either the laboratory, field or computational resources.…”
Section: Implications For Transport Rate Predictionmentioning
confidence: 99%
“…Recent work by Kirchner et al (1990) and Buffington et al (1992) has addressed the problem of describing the entrainment of mixed-grain-size sediments in probabilistic terms. They measured friction angles of particles placed on the surface of a mixed-grain-size sediment bed by tilting the bed to an angle at which a particle of interest moved from its position.…”
Section: The Grain Mechanics Perspectivementioning
confidence: 99%
“…Though Brahms suggested in 1753 that the velocity for incipient motion is proportional to the grain weight raised to the sixth power, this condition is more appropriately analyzed from the concept of a balance of forces acting upon a particle. Incipient motion, however, has further complexities due to the fluctuating characteristics (turbulence) of the flow over a bed of sediment, composed of innumerable particles of various shapes, sizes, orientation, specific weight, protrusion, roughness, and location (Kirchner et al, 1990). Also, incipient motion is influenced by material gradation, friction angle, sorting, and armoring of the bed (Forchheimer, 1914;Buffington, Dietrick, and Kirchner, 1992).…”
Section: Initiation Of Motion Of Substrate Particlementioning
confidence: 99%